2014
DOI: 10.1186/1471-2458-14-1315
|View full text |Cite
|
Sign up to set email alerts
|

Supporting health promotion practitioners to undertake evaluation for program development

Abstract: BackgroundThe vital role of evaluation as integral to program planning and program development is well supported in the literature, yet we find little evidence of this in health promotion practice. Evaluation is often a requirement for organisations supported by public funds, and is duly undertaken, however the quality, comprehensiveness and use of evaluation findings are lacking. Practitioner peer-reviewed publications presenting evaluation work are also limited. There are few published examples where evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 34 publications
6
49
0
7
Order By: Relevance
“…However, only a small number of evaluations of Indigenous health promotion tools, of generally moderate quality, have been undertaken 13 . While evaluation challenges are faced by all health promotion practitioners, 16 additional challenges may be experienced in the course of evaluating Indigenous health promotion tools due to issues typically present in rural/remote and Indigenous health settings. These issues include frequent workforce turnover; staff overloaded with multiple responsibilities (thus having limited capacity to pursue evaluations); limited funding; and short time‐frame of projects in general 17 .…”
Section: Discussionmentioning
confidence: 99%
“…However, only a small number of evaluations of Indigenous health promotion tools, of generally moderate quality, have been undertaken 13 . While evaluation challenges are faced by all health promotion practitioners, 16 additional challenges may be experienced in the course of evaluating Indigenous health promotion tools due to issues typically present in rural/remote and Indigenous health settings. These issues include frequent workforce turnover; staff overloaded with multiple responsibilities (thus having limited capacity to pursue evaluations); limited funding; and short time‐frame of projects in general 17 .…”
Section: Discussionmentioning
confidence: 99%
“…To generate evidence to improve health promotion practice, evaluation needs to be conducted throughout the implementation of an intervention not only at the conclusion. 20 A multifaceted evaluation plan is required to assess the complex web of components that could impact on the success of an mHealth intervention.…”
Section: Mobile Apps and Health Promotionmentioning
confidence: 99%
“…This encompassed three stages of evaluation: formative (takes place while planning interventions), process (takes place during the implementation) and impact (assesses the outcomes of the intervention) evaluation. 20,26 Milk Man is the first breastfeeding app we are aware of that targets fathers. The development of the app included formative evaluation with input from the target group and health professionals, and a usertesting phase encompassing a think-aloud walkthrough and completion of the MARS.…”
Section: Milk Man Evaluation Planmentioning
confidence: 99%
“…Comprehensive evaluation requires time, appropriate skills of the evaluators, collaboration with project partners and stakeholders, and adequate resources . Building pertinent evaluation skills is a critical component of workforce development.…”
Section: Introductionmentioning
confidence: 99%
“…The first was staff evaluation knowledge and skills. The second was an organisational focus on achievement of a program's purpose rather than satisfying auditing requirements; and the third was translation and sharing of evaluation findings to shape future practice . Other studies have shown that staff trained in health promotion have difficulty translating new learnings into practice without organisational support .…”
Section: Introductionmentioning
confidence: 99%